Virtual OSCE Delivery and Quality Assurance During a Pandemic: Implications for the Future - Saad, Shannon L.; Richmond, Cassandra; Jones, Karina; Schlipalius, Michelle; Rienits, Helen; Malau-Aduli, Bunmi S. (Frontiers in Medicine, 2022)
Background During 2020, the COVID-19 pandemic caused worldwide disruption to the delivery of clinical assessments, requiring medicals schools to rapidly adjust their design of established tools. Derived from the traditional face-to-face Objective Structured Clinical Examination (OSCE), the virtual OSCE (vOSCE) was delivered online, using a range of school-dependent designs. The quality of these new formats was evaluated remotely through virtual quality assurance (vQA). This study synthesizes the vOSCE and vQA experiences of stakeholders from participating Australian medical schools based on a Quality framework. Methods This study utilized a descriptive phenomenological qualitative design. Focus group discussions (FGD) were held with 23 stakeholders, including examiners, academics, simulated patients, professional staff, students and quality assurance examiners. The data was analyzed using a theory-driven conceptual Quality framework. Results The vOSCE was perceived as a relatively fit-for purpose assessment during pandemic physical distancing mandates. Additionally, the vOSCE was identified as being value-for-money and was noted to provide procedural benefits which lead to an enhanced experience for those involved. However, despite being largely delivered fault-free, the current designs are considered limited in the scope of skills they can assess, and thus do not meet the established quality of the traditional OSCE. Conclusions Whilst virtual clinical assessments are limited in their scope of assessing clinical competency when compared with the traditional OSCE, their integration into programs of assessment does, in fact, have significant potential. Scholarly review of stakeholder experiences has elucidated quality aspects that can inform iterative improvements to the design and implementation of future vOSCEs.